Manipulation of the Magnetoresistance by Strain in Topological TaSe3. Issue 12 (17th October 2022) - Xing, Jie; Blawat, Joanna; Speer, Smita; Saleheen, Ahmad Ikhwan Us; Singleton, John; Jin, Rongying
Abstract: 1D TaSe3 exhibits many unusual physical properties due to its distorted type‐II chains. Ribbon‐shaped single crystals can be easily bended along the b ‐axis, forming rings. This study investigates the magnetoresistance (MR) of TaSe3 up to 60 T in both unbended (ribbon shape) and ring‐shaped (bended ribbon) samples. Notable changes are found in the magnetotransport properties between the two different shaped samples. One is that the MR in ring‐shaped samples is three orders lower than that in unbended samples under the same sample environment. In addition, linear MR is observed above ≈20 T in ring‐shaped samples when the magnetic field is parallel or perpendicular to the rings. Quantum oscillations are also observed as a function of the magnetic field when the magnetic field is applied parallel to rings, possibly due to the Altshuler–Aronov–Spivak effect or the inversion of the lowest Landau level beyond the quantum limit. All these results are related to strain‐induced electronic structure change in TaSe3, an effective way to tune physical properties in low‐dimensional materials. Abstract : 1D TaSe3 single crystals can be bended along its b ‐axis forming rings. Its magnetotransport properties reveal different behavior than the unbended case, including linear magnetoresistance and quantum oscillations as a function of the magnetic field when the field is parallel to the rings. These results indicate that shape manipulation is an effective way to tune physical properties of TaSe3 .